A study of direct powder rolling route for CP-titanium - Zhang, Yu (Centre for Materials Engineering, 2016)
Titanium and its alloys have extremely high strength to weight ratio and corrosion resistance. This has made titanium alloys very attractive materials for many structural applications. However, the high price of these alloys has seen their use restricted to very few high performance areas such as aerospace and bio-medical applications. The costs can be significantly reduced by directly converting titanium powder to metal products, particularly via the direct powder rolling process. This present research is based on a parametric study of powder rolling and operational effects including rolling speed, roll gap size, roll surface width and powder feeding rate on the integrity of the metal powder compacted strip that is produced from the direct powder rolling process. The objectives of this work were to predict the powder rolling compaction performance in terms of compaction pressure, roll surface force and rolling torque, and produce the highest possible relative density of CP-titanium green strips by optimized rolling variable setups, and to achieve its full density by additional hot deformation processing. In this work, a purpose-built gravity fed vertical powder rolling mill with a roller diameter of 265 mm and a roller width of 150 mm was used. Johanson's powder rolling model has been implemented to simulate performance and a series of rolling parameter setups have been conducted by the using a purpose-built powder rolling mill. Pre-alloyed, water-atomized stainless steel 316L powder and hydride-dehydride (HDH) CP-titanium powders with a mean particle size of 100 μm were used as the experimental material to validate the simulated results in terms of relative density and strip dimensions. The powder rolling experiments were carried out based on the Johanson's powder rolling model to conduct a parametric experimental study in various setups of powder rolling parameter combinations, including roll gap, roll face width, rolling speed and powder feeding rate.